The Influence of Digital Marketing, Destination Image, and Facilities on Visitor Satisfaction in Islamic Business Perspective - Dina Mardiana Astuti; Muhammad Iqbal Fasa; Yeni Susanti Susanti (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of Digital Marketing, destination image, and facilities on Visitor decisions in Lanakila Lake Pringsewu tourism, in the perspective of Islamic Business. This study uses a quantitative approach. The population used by a total of 4000 tourist visitors Lanakila Lake and by Slovin formula was selected 98 respondents. Based on the test results that have been done, there are findings that can be concluded that Digital marketing has a positive and significant effect on visitor satisfaction, destination image has a positive and significant effect on visitor satisfaction and facility variables have a positive and significant effect on visitor satisfaction. And in the view of Islamic business when all three aspects are run in an integrated manner with Islamic values, visitors will feel satisfaction not only in terms of physical and emotional, but also spiritual which must contain two main principles in Islamic business, namely amanah (carrying out responsibilities correctly) and ‘adl (upholding justice.).